2010
DOI: 10.1097/inf.0b013e3181f68e9c
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Single Administration of Live-attenuated Japanese Encephalitis Vaccine in Previously Primed 2- to 5-year-olds and Naive 12- to 24-month-olds

Abstract: A single administration of JE-CV has a good safety profile and elicits a protective immune response in both JE-naive toddlers and JE-primed young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 30 publications
10
70
0
Order By: Relevance
“…Indeed, clinical trials have shown that YF17D-JE is safe and immunogenic with a single dose providing long-lasting immunity to wild-type strains of JE virus. [48][49][50][51] This recombinant technology-based vaccine was licensed for human use in Australia (Imojev-Sanofi-Pasteur). Accordingly, YF17D-WN chimeric viruses have also undergone clinical tests.…”
Section: Replacement Of Yf17d Structural Genes With Those Of Other Flmentioning
confidence: 99%
“…Indeed, clinical trials have shown that YF17D-JE is safe and immunogenic with a single dose providing long-lasting immunity to wild-type strains of JE virus. [48][49][50][51] This recombinant technology-based vaccine was licensed for human use in Australia (Imojev-Sanofi-Pasteur). Accordingly, YF17D-WN chimeric viruses have also undergone clinical tests.…”
Section: Replacement Of Yf17d Structural Genes With Those Of Other Flmentioning
confidence: 99%
“…A Phase I RCT trial 27 including yellow fever (YF)-immune (n D 18) and non-YF-immune (n D 18) subjects showed the immunogenicity of a single dose of JE-CV at 2 different dosages (5.0 log 10 PFU vs. 4.0 log 10 PFU) was comparable to YF-VAX In a Phase II trial 28 with 99 adults in the USA, the immunogenicity of graded doses of JE-CV (1.8-5.8 log 10 PFU) was evaluated. 82 (94%) of 87 subjects administered JE-CV developed neutralizing antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Nakayama vs. Beijing-1 or SA14-14-2, or any of these vs. other wild-type G-III strains) with MBDI, SA14-14-2 LAV, JE-CV as well as Vero CCDI vaccines, although the differences in SCRs or GMTs are not significant statistically. 22,24,25,27,31,65,70,71,117,120,122,136,[165][166][167] This differential neutralization as well as protection against G-III viruses has also been shown in mouse challenge studies. 168 Other studies have shown no such differences or higher GMTs with the heterologous virus strains.…”
Section: Cross-reactivity and Cross-protection Of Antibody Responses mentioning
confidence: 99%
“…In general, these studies have shown that NAb titres are highest against G-II and homologous G-III viruses, followed by G-IV and heterologous G-III viruses, whereas titres against G-I viruses are the lowest, and in some cases below protective levels. 22,[24][25][26][27][28][29] A recent study specifically evaluated the ability of a G-III virus to elicit protective responses in mice, and the ability of human post-vaccinal and acute phase sera to neutralize G-V viruses. The study found that (a) NAb titres in mice immunized with either G-III or G-V virus were higher with homologous viruses but poor against G-V, (b) the SA14-14-2 LAV or the P-3 inactivated vaccines were less protective against G-V virus challenge in mice, and (c) both GMTs and SPRs were poor against G-V virus, intermediate against G-I virus, and highest against G-III virus with both post-vaccinal and acute phase human sera.…”
Section: Cross-reactivity and Cross-protection Of Antibody Responses mentioning
confidence: 99%
See 1 more Smart Citation